2014
DOI: 10.1371/journal.pone.0112269
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Gossypium hirsutum Sucrose Non-Fermenting 1-Related Protein Kinase 2 Gene (GhSnRK2) and Its Overexpression in Transgenic Arabidopsis Escalates Drought and Low Temperature Tolerance

Abstract: The molecular mechanisms of stress tolerance and the use of modern genetics approaches for the improvement of drought stress tolerance have been major focuses of plant molecular biologists. In the present study, we cloned the Gossypium hirsutum sucrose non-fermenting 1-related protein kinase 2 (GhSnRK2) gene and investigated its functions in transgenic Arabidopsis. We further elucidated the function of this gene in transgenic cotton using virus-induced gene silencing (VIGS) techniques. We hypothesized that GhS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…Under salt stress, levels of SOD, CAT, POD, and GSSG contents in transgenic line plants were higher than levels in WT plants (Figure 2), indicating that ThTrx5 overexpression increased salt tolerance of A. thaliana. This result aligns with previously reported results demonstrating that transgenic Arabidopsis overexpressing GhSnRK2 showed obvious salt tolerance that was associated with stress response processes that reduced water loss, regulated cell turgor, maintained relative water content, and controlled proline accumulation [18]. In fact, the importance of glutathione to plant salt stress responses has also been demonstrated in tomato, as glutathione content increased significantly under high salt exposure [19].…”
Section: Overexpressing Thtrx5 Improves Salt Resistance Of Arabidopsisupporting
confidence: 92%
“…Under salt stress, levels of SOD, CAT, POD, and GSSG contents in transgenic line plants were higher than levels in WT plants (Figure 2), indicating that ThTrx5 overexpression increased salt tolerance of A. thaliana. This result aligns with previously reported results demonstrating that transgenic Arabidopsis overexpressing GhSnRK2 showed obvious salt tolerance that was associated with stress response processes that reduced water loss, regulated cell turgor, maintained relative water content, and controlled proline accumulation [18]. In fact, the importance of glutathione to plant salt stress responses has also been demonstrated in tomato, as glutathione content increased significantly under high salt exposure [19].…”
Section: Overexpressing Thtrx5 Improves Salt Resistance Of Arabidopsisupporting
confidence: 92%
“…Some members in the hormone signaling pathway have been identified to participate in the response to salt stress. It has been reported that overexpressing of G. hirsutum sucrose non-fermenting 1-related protein kinase 2 (GhSnRK2), which acts as a positive regulator in ABA signaling pathway, exhibited increased tolerance to ABA and salt stresses [45]. However, the molecular basis of cotton tolerance to salt stress remains to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Among different abiotic stresses, drought and salinity are the two main factors that affect the cotton production and it has become a challenging task to improve tolerance in cotton against these stresses. Previously, few stress-related genes such as GhCIPK6 (He et al, 2013), GbRLK (Zhao et al, 2013), GhMKK1 (Lu et al, 2013) and GhSnRK2 (Bello et al, 2014) have been reported in cotton (Table 3). A cotton Raf-like MAP3K (GhMAP3K40) gene positively regulates defence response but mediates reduced tolerance to biotic and abiotic stresses in transgenic Nicotiana benthamiana .…”
Section: Abiotic Stressesmentioning
confidence: 99%
“…However, the overexpression of annexin-encoding (GhAnn1) gene showed higher chlorophyll content, increased peroxidase activities and lower lipid peroxidation levels, which ultimately increase the salt and drought stress tolerance in transgenic cotton . Previous studies have also reported that CBL-interacting protein kinase (GhCIPK6) and sucrose nonfermenting 1-related protein kinase 2 (SnRK2) genes are also involved in abiotic stress tolerance in cotton (Bello et al, 2014;He et al, 2013). Genes related to ethylene, abscisic acid and jasmonic acid signalling pathways have also played a significant role in drought tolerance .…”
Section: Abiotic Stressesmentioning
confidence: 99%